Limites e potencialidades da coleta seletiva de resíduos sólidos em municípios de médio porte: o caso de Barreiras – BA - Silva, Pollyana Ferreira da (Universidade Federal de São Carlos, 2018)
The management of solid urban waste (MSUW) is a challenge for many brazilian municipalities. In this sense, the National Solid Waste Policy (NSWP) includes instruments such as selective collection, reverse logistics, the insertion of waste collector cooperatives and the sectoral agreements to be used in Municipal Solid Waste Management (MSWM) Municipal Plans as mechanisms management. The present work has the objective of evaluating the limits and the potentialities of the selective collection in the municipality of Barreiras - BA. In order to reach the proposed objective, an evaluation of the MSWM was made, with emphasis on aspects related to selective collection. In addition, the social actors relevant to MSUW were identified and the reading of the selected actors on the research topic was investigated using structured interviews. Concomitantly, data collection forms were applied in institutions linked to selective collection and reverse logistics to characterize them. At the same time, the direct observation was carried out to describe the details of the environments, contexts and facts of the selective collection. The analysis of the limits and potentialities of the selective collection was made from the synthesis of the obtained results, using as tool the SWOT matrix. We obtain a scenario matrix that indicates the strengths, weaknesses, opportunities and threats studied. The guidelines were elaborated in the possession of all the results, from the exercise of critical reflection of the researchers. Thus, it was verified that MSWM/2014 is a plan adequate to the aspirations of a selective collection system, but it is necessary to review its fragilities related to the prioritization of public policies for recyclable waste pickers, reduction of MSW and the definition of municipal public power attributions in the selective collection and reverse logistics. The selective collection takes place in different environments, in the streets through autonomous pickers, in the city dump, in the cooperative and association of collectors. This activity in the city recovers 450 t./month of waste (which corresponds to the annual per capita mass of 34 Kg/hab./year) and generates an income of 500 thousand reais. However, two limiting factors for collection are the precariousness of the institutions and the informal work of autonomous scavengers. Regarding Reverse Logistics - RL, 73% of the consulted companies do not practice it and have shown a lot of ignorance about the subject, which makes LR very incipient. However, there are 4 ENPs and 9 technical assists that maintain this service for the post consumer products. This scenario can be better evaluated in the SWOT matrix, where it was concluded that the main limitations are the lack of political initiative, recycling industries and the logistical difficulty of selling recyclables. And the most latent potentialities are the regionalization of the recyclable trade and the possibility of expanding the selective collection in the municipality (53%). This environment of analysis has indicated that there are more weaknesses than strengths and more opportunities than threats. Thus, favorable internal and external environmental conditions exist for the city to include selective collection as a practice of MSW management.
Limits and potentialities of the selective collection of solid waste in middle municipalities: the case of Barreiras - BA
Keywords: Coleta seletiva; Logística reversa; Planos municipais de gestão integrada de resíduos sólidos; Selective collection; Reverse logistics; Municipal plans for integrated solid waste management; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL